2009
DOI: 10.1088/0004-637x/692/1/556
|View full text |Cite
|
Sign up to set email alerts
|

Determining Star Formation Rates for Infrared Galaxies

Abstract: We show that measures of star formation rates (SFRs) for infrared galaxies using either singleband 24µm or extinction-corrected Paα luminosities are consistent in the total infrared luminosity = L(TIR) ∼ 10 10 L ⊙ range. MIPS 24µm photometry can yield star formation rates accurately from this luminosity upward: SFR(M ⊙ yr −1 )=7.8 × 10 −10 L(24µm, L ⊙ ) from L(TIR) = 5× 10 9 L ⊙ to 10 11 L ⊙ and SFR = 7.8 × 10 −10 L(24µm, L ⊙ )(7.76 × 10 −11 L(24)) 0.048 for higher L(TIR). For galaxies with L(TIR) ≥ 10 10 L ⊙ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

87
1,155
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 607 publications
(1,247 citation statements)
references
References 121 publications
(205 reference statements)
87
1,155
5
Order By: Relevance
“…Another set of templates used extensively by the DSFG community are those described in Rieke et al (2009). Rieke et al use detailed Spitzer observations of eleven local LIRGs and ULIRGs to construct a library of templates spanning 0.4µm-30 cm and luminosities 5×10 9 -10 13 L .…”
Section: Direct Fir-only Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another set of templates used extensively by the DSFG community are those described in Rieke et al (2009). Rieke et al use detailed Spitzer observations of eleven local LIRGs and ULIRGs to construct a library of templates spanning 0.4µm-30 cm and luminosities 5×10 9 -10 13 L .…”
Section: Direct Fir-only Methodsmentioning
confidence: 99%
“…the "Santa Cruz SAM") that was combined with estimates for dust attenuation by both diffuse dust and stellar birth clouds surrounding young clusters. The energy absorbed by dust was assumed to be re-radiated in the infrared, and combined these with both theoretical SED templates by Devriendt et al (1999), as well as the locally-calibrated observed SED templates by Rieke et al (2009). These authors found that in order to reproduce the (rest) UV and optical luminosity functions at high-z, an evolving dust-to-metals ratio was necessary.…”
Section: Semi-analytic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider the theoretical approach taken in Somerville et al (2011) and Gilmore et al (2011) Charlot & Fall (2000); Dust re-emission: templates by Rieke et al (2009) (ii) Backward evolution, e.g., Franceschini et al (2008) Observed local-optical galaxy luminosity function (LF, for starburst population) and near-IR galaxy LF observed up to z = 1.4 (for elliptical and spiral populations)…”
Section: Introductionmentioning
confidence: 99%